Experiences of Older People Living with Frailty Transitioning from Hospital to Home — A Qualitative Descriptive Study - Tran, Jake; Das, Shayandeep; Nguyen, Anh; Frew, Melissa; Woo, Kevin (Journal of Posthumanism, 2025)
This qualitative study explores the experiences of older people living with frailty, their informal caregivers, healthcare professionals, and administrators during the transition from hospital to home within the Ontario Health Teams (OHT) model. Using focus group discussions (FG1: older adults and caregivers, FG2: healthcare administrators, and FG3: healthcare professionals), the study identifies six key themes critical to successful care transitions: 1) healthcare as holistic care, 2) the therapeutic value of familiar surroundings, 3) the need for patient and caregiver voice and choice, 4) the challenges of navigating the disconnect between hospital and community care, 5) the importance of supporting informal caregivers, and 6) the impact of income, language, and equity on care access. The findings highlight significant communication, coordination, and resource allocation gaps impeding effective transitions. Such problems are associated with emotional strains of patients, caregivers, and health care providers, and higher chances of caregiver burnout and hospital readmission. The paper highlights the necessity of integrated, patient-centred care models, in which a smooth transition, effective communication, and active participation of patients and caregivers in the care planning are essential. A solution to these issues is the proposed Integrated Transitional Care Model (ITCM), based on the insights of the study, to enhance care coordination, decrease readmissions, and offer equitable care to older adults who may be frail. The study highlights the need to develop a collaborative healthcare system in which all stakeholders, including patients, caregivers, medical practitioners, and administrators, collaborate to facilitate smooth and well-coordinated transitions and better health results. The results present meaningful policy, practice, and research implications to improve care transitions of frail older adults in Ontario and elsewhere.